A DFT study of the hydrolysis of hydantoin. Issue 11 (5th August 2019) - Yamabe, Shinichi; Tsuchida, Noriko; Yamazaki, Shoko
Abstract: Density functional theory (DFT) calculations were made on the hydrolysis of hydantoin (2, 4‐imidazolidinedione). In the neutral hydrolysis, reacting systems composed of hydantoin and (H2 O) n with n = 1+3, 2+3, 3+3, and 4+3 were adopted. Three water molecules ("+3") participate in the in‐plane hydrogen‐bond circuit, and the n –3 = 1, 2, 3 or 4 water cluster works for the out‐of‐plane nucleophilic attack onto the carbonyl carbon of hydantoin. Transition states (TSs) involving bond interchanges prompted by proton transfers were determined. The reaction path with n = 3+3 containing N ‐carbamoyl glycine, N ‐carboxy glycine and three tetrahedral intermediates was found to be most likely. In the acid‐catalyzed hydrolysis, a reacting system composed of hydantoin and H3 O + (H2 O)7 was employed. Ten TSs and nine intermediates were obtained. N ‐carbamoyl glycine and N ‐carboxy glycine were confirmed to be detectable stable species. The product consists of glycine, carbonic acid (not CO2 ), NH4 +, and (H2 O)5 . It has the exothermic energy, whereas the product in the neutral hydrolysis is of the endothermic one for all n values. For both neutral ( n = 3+3) and acid‐catalyzed hydrolyses, the rate‐determining steps were calculated to be for formation of the tetrahedral intermediate, HOOC‐CH2 ‐NH‐C(OH)2 NH2 . The pattern of proton transfers along hydrogen bonds was carefully investigated.